2008
DOI: 10.1111/j.1467-9280.2008.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Preferentially Enhances Memory for Emotional Components of Scenes

Abstract: Central aspects of emotional experiences are often well remembered at the expense of background details. Previous studies have focused on memory after brief delays, but little is known about how these components of emotional memories change over time. Here we investigated the evolution of negative scene memories across 30 minutes, 12 daytime hours spent awake, or 12 nighttime hours including sleep. Negative objects were well remembered at the expense of their backgrounds after 30min. Time spent awake led to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
434
10
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(494 citation statements)
references
References 31 publications
30
434
10
2
Order By: Relevance
“…Although this type of protocol has been extensively used in prior studies (e.g. Hu et al, 2006;Payne et al, 2008), we need to rule out circadian influences in our measurements. Firstly, there was no significant group difference in objective (PVT) and subjective (KSS) vigilance levels across experimental sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this type of protocol has been extensively used in prior studies (e.g. Hu et al, 2006;Payne et al, 2008), we need to rule out circadian influences in our measurements. Firstly, there was no significant group difference in objective (PVT) and subjective (KSS) vigilance levels across experimental sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance to the schedule was assessed using a sleep diary and wrist actigraphy (Actiwatch, Cambridge Neuroscience, Cambridge, UK). Because we aimed at minimizing any experimental stressors (see Results section), the participants from the Sleep group slept in familiar conditions at their home with actimetry (but no EEG) (Hu et al, 2006;Payne et al, 2008).…”
Section: General Experimental Designmentioning
confidence: 99%
“…Positive effects of sleep on emotional memories have been reported at the behavioral level. Retrieval of emotional (relative to neutral) material several hours after encoding is enhanced if the interval contains an episode of sleep (Hu et al, 2006;Payne et al, 2008;Nishida et al, 2009), especially rapid eye movement (REM) sleep (Wagner et al, 2001), rather than a period of wake. This sleep-dependent advantage persists 4 years later (Wagner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional stimuli are known to influence memory processes at various levels, beginning at encoding and extending to consolidation and retrieval stages (Payne, Stickgold, Swanberg, & Kensinger, 2008;Phelps, 2004). Several studies have demonstrated boosts in recollection (Ochsner, 2000) and in memory for details of negative visual scenes and objects (Canli, Zhao, Brewer, Gabrieli, & Cahill, 2000;Kensinger, Garoff-Eaton, & Schacter, 2007a, 2007b.…”
mentioning
confidence: 99%